2022
DOI: 10.1177/02676591221095469
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hemocompatibility screening of a slippery liquid impregnated surface coating for extracorporeal organ support applications

Abstract: Introduction: Clot formation, infection, and biofouling are unfortunate but frequent complications associated with the use of blood-contacting medical devices. The challenge of blood-foreign surface interactions is exacerbated during medical device applications involving substantial blood contact area and extended duration of use, such as extracorporeal life support (ECLS). We investigated a novel surface modification, a liquid-impregnated surface (LIS), designed to minimize protein adsorption and thrombus dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Significantly, we demonstrated that these thin TLP layers prevent the adhesion of human whole blood (platelets and fibrinogen), both under static conditions (seen previously) and shear flow. These results are consistent with previous findings in the literature that reported the repellence of fibrinogen and platelets on TLP coatings. ,,, …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Significantly, we demonstrated that these thin TLP layers prevent the adhesion of human whole blood (platelets and fibrinogen), both under static conditions (seen previously) and shear flow. These results are consistent with previous findings in the literature that reported the repellence of fibrinogen and platelets on TLP coatings. ,,, …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous findings in the literature that reported the repellence of fibrinogen and platelets on TLP coatings. 8,15,38,39 TLP coatings could find clinical application in devices and components intended for short-term or transient usage and/or in devices with lower flow or stagnant flow regions. The method described here allows us to relate the performance of TLP in near-clinical flow conditions to the presence and distribution of lubricants, in settings that are challenging to characterize otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…100 In extracorporeal circuits, in vivo studies for 6 and 8 hours demonstrated the antithrombogenic properties of LIS. 103,105,108 However, on extracorporeal circuits exposed to blood for 72 hours, the coatings were reported to have failed. 109 The authors have attributed blood flow for extended durations as a possible reason, leading to the loss of lubricant, resulting in thrombus deposition.…”
Section: Liquid-infused Surfacesmentioning
confidence: 99%
“…[23][24][25][26] Beyond systemic anticoagulation, most efforts to further address these complications are directed toward mitigating surface-induced activation of the blood, via application of anti-thrombotic surface treatments applied to the HFMO cartridge and to associated tubing and other circuit elements. [27][28][29] However, another major cause of hemocompatibility issues in ECMO stems from the presence of non-physiologic blood flows in the circuit [30][31][32][33] : regions of excessive shear stress, zones of blood stasis, and transition regions, all serving as a nidus for clot formation. The fundamental geometry of HFMO cartridges, in which blood flows through large bore plastic tubes and over oxygen-carrying fiber mats within a large housing, limits the ability to precisely control blood flow circulation patterns or shear rates on a local level.…”
Section: Introductionmentioning
confidence: 99%